Diversificación productiva, geográfica y por deudores y su efecto sobre la calidad de la cartera crediticia en Argentina - Alejandra Anastasi; Ricardo Bebczuk; Pedro Elosegui; Máximo Sangiácomo (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2008)
– This paper analyzes the relationship between the quality of the commercial credit portfolio and diversification in the financial entities of Argentina during the period 1998-2006. To this effect, a database of the financial sector (banking and non-banking) is used, which allows to consider three potential dimensions of diversification: per productive sector, per province and per client. In addition to characterizing the financial entities' diversification decisions during the period under analysis, which includes the severe economic and financial crisis of late 2001, the paper analyzes the determinants of the portfolio's quality including the effect of diversification in the three dimensions stated above. The results indicate that, by controlling for the relevant variables, specialization improves the quality of the credit portfolio.
Keywords: C23; G21; G23; 330; Argentina; banks; credit diversification; loan quality; non-performing loans; Bankrisiko; Diversifikation; Argentinien